Effect of salinomycin on performance of grazing stocker heifers - Lyle W. Lomas (Kansas Agricultural Experiment Station Research Reports, 1986)
The effect of feeding 0, 25, 50, 100, or 150 mg of salinomycin per head daily on performance of stocker heifers grazing smooth bromegrass pasture was evaluated in a 126-day trial. Feeding 100 or 150 mg of salinomycin per head daily produced the fastest gain.
Keywords: Cattlemen& #x27; s Day; 1986; Kansas Agricultural Experiment Station contribution; no. 86-320-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 494; Beef; Salinomycin; Performance; Stocker heifers